Copolymerization of N-Phenyl Citraconimide with Methyl Methacrylate - Tyagi, Hemant; Tyagi, D.S.; Tyagi, Pankaj; Tyagi, Parul (Asian Journal of Chemistry, 2010)
Synthesis and characterization of copolymers prepared by N-phenyl citraconimide, N-(o/m/pchlorophenyl) citraconimide and N-(p-tolyl) citraconimide with methyl methacrylate (MMA) by using controlled free radical initiation (ATRP).